Human Red Blood Cells Modulate Cytokine Expression in Monocytes/Macrophages Under Anoxic Conditions - Antonelli, Antonella; Scarpa, Emanuele S.; Magnani, Mauro (Frontiers in Physiology, 2021)
In the bone marrow hematopoietic niche, the oxygen tension is usually very low. Such condition affects stem and progenitor cell proliferation and differentiation and, at cellular level regulates hematopoietic growth factors, chemokines and adhesion molecules expression. In turn, these molecules affect the proliferation and maturation of other cellular components of the niche. Due to the complexity of the system we started the in vitro investigations of the IL-6, IL-8, TNF cytokines expression and the vascular endothelial growth factor (VEGF), considered key mediators of the hematopoietic niche, in human macrophages and macrophage cell line. Since in the niche the oxygen availability is mediated by red blood cells (RBCs), we have influenced the anoxic cell cultures by the administration of oxygenated or deoxygenated RBCs. The results reported in this brief paper show that the presence of RBCs up-regulates IL-8 mRNA while IL-6 and VEGF mRNA expression appears down-regulated. This does not occur when deoxygenated RBCs are used. Moreover, it appears that the administration of RBCs leads to an increase of TNF expression levels in MM6 cells. Interestingly, the modulation of these factors likely occurs in a hypoxia-inducible factor-1 (HIF-1) independent manner. Considering the role of oxygen in the hematopoietic niche further studies should explore these preliminary observations in more details.